Healing livers, saving lives: Hepatitis C screening in an era of cure. Issue 5 (May 2016) - Boucher, Courtney M.; Walsh, Anne; Forest, Christopher P.
Abstract : ABSTRACT: Chronic hepatitis C affects more than 3 million people in the United States. In the past, drug therapy with interferon and ribavirin resulted in low overall cure rates and early discontinuation due to adverse reactions. The new direct-acting antivirals offer not only a shorter duration of treatment with fewer adverse reactions, but greatly improved overall cure rates as high as 96%. Updated national screening recommendations (including a one-time screening for patients born between 1945 and 1965), combined with timely referral and treatment, offer a prime opportunity for healthcare providers to improve public health outcomes and reduce healthcare costs.